Modern and traditional irrigation technologies in the eastern Mediterranean - Mehmet, Ozay, 1938-; Biçak, Hasan Ali (International Development Research Centre, 2002)
A water crisis is threatening several regions of the world. In the Middle East and North Africa, the crisis is serious and getting worse. Contributing factors include mismanagement of water resources, population trends and explosive urban growth, structural imbalance between demand and available resources, and a dearth of water-related information. This book presents an analysis of irrigation technologies used in the Eastern Mediterranean region, both past and present. It discusses the reuse of wastewater and other conservation technologies through case studies from Israel, Jordan, Lebanon, No.